Properties of DLC films deposited by an oxyacetylene flame - Doi, I; Haga, M. S.; Nagai, Y. E. (Elsevier B.V., 1999)
Diamond-like carbon (DLC) films were obtained by spinning a tungsten carbide substrate at a high speed using an oxyacetylene flame. The films deposited at a typical experimental condition of substrate temperature of 810 degrees C, rotation of 600 rpm and 3 h deposition time, exhibited an uniform, very smooth, hard and glassy surface covering the entire exposed face of the substrate. These films were identified as DLC by their characteristic broad Raman spectra centered at 1554 cm(-1) and micro-Vicker's hardness > 3400 kg mm(-2). For substrate temperatures < 800 degrees C the film started losing the uniform glassy surface and the hardness deteriorated. For temperatures > 950 degrees C the film was still hard and shiny, but black in color. DLC films were also obtained in a wide range of speeds of rotation (300-750 rpm), as long as the temperature remained close to 850 degrees C. (C) 1999 Elsevier B.V. S.A. All rights reserved.
Keywords: amorphous carbon; combustion synthesis; deposition; diamond-like carbon